![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) ( 4x - 1 ) ( x - 2 ) = 0
\(\Leftrightarrow\orbr{\begin{cases}4x-1=0\\x-2=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{4}\\x=2\end{cases}}\)
Vậy \(x\in\left\{\frac{1}{4};2\right\}\)
b) 4x2 - 12x = 0
<=> 4x ( x - 3 ) = 0
\(\Leftrightarrow\orbr{\begin{cases}4x=0\\x-3=0\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x=0\\x=3\end{cases}}\)
Vậy \(x\in\left\{0;3\right\}\)
c) ( x - 5 )4 + 25 - x2 = 0
( x - 5 ) 4 + ( 5 - x ) ( 5 + x ) = 0
( x - 5 ) ( 4 + 5 + x ) = 0
( x - 5 ) ( 9 + x ) = 0
\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\9+x=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=5\\x=-9\end{cases}}\)
Vậy \(x\in\left\{-9;5\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, <=> (x-2)2=25
<=>x-2=5 hoặc x-2=-5
<=>x=7 hoặc x=-3
c,<=>(x2)2-16=0
<=>(x2)2=16
<=>x2=4
<=>x=2 hoặc x=-2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(4x^2-12x=-9\)
\(\Leftrightarrow4x^2-12x+9=0\)
\(\Leftrightarrow\left(2x-3\right)^2=0\)
\(\Leftrightarrow2x-3=0\Leftrightarrow x=\frac{3}{2}\)
b) \(\left(5-2x\right)\left(2x+7\right)=4x^2-25\)
\(\Leftrightarrow\left(5-2x\right)\left(2x+7\right)+\left(25-4x^2\right)=0\)
\(\Leftrightarrow\left(5-2x\right)\left(2x+7\right)+\left(5-2x\right)\left(5+2x\right)=0\)
\(\Leftrightarrow\left(5-2x\right)\left(2x+7+5+2x\right)=0\)
\(\Leftrightarrow\left(5-2x\right)\left(4x+12\right)=0\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=\frac{5}{2}\\x=-3\end{array}\right.\)
c)\(x^3+27+\left(x+3\right)\left(x-9\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(x^2-3x+9\right)+\left(x+3\right)\left(x-9\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(x^2-3x+9+x-9\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(x^2-2x\right)=0\)
\(\Leftrightarrow\left(x+3\right)x\left(x-2\right)=0\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-3\\x=0\\x=2\end{array}\right.\)
d) \(4\left(2x+7\right)^2-9\left(x+3\right)^2=0\)
\(\Leftrightarrow\left[2\left(2x+7\right)-3\left(x+3\right)\right]\left[2\left(2x+7\right)+3\left(x+3\right)\right]=0\)
\(\Leftrightarrow\left(4x+14-3x-9\right)\left(4x+14+3x+9\right)=0\)
\(\Leftrightarrow\left(x+5\right)\left(7x+23\right)=0\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-5\\x=-\frac{23}{17}\end{array}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) \(4x^2+4x+1=\left(2x+1\right)^2\)
2)\(9x^2-24xy+16y^2=\left(3x-4y\right)^2\)
3)\(-x^2+10x-25=-\left(x-5\right)^2\)
4)\(1+12x+36x^2=\left(1+6x\right)^2\)
5) \(\dfrac{x^2}{4}+2xy+4y^2=\left(\dfrac{x}{2}+2y\right)^2\)
6) \(4x^2+4xy+y^2=\left(2x+y\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\Rightarrow25\left(x+1\right)^4-26\left(x+1\right)^2+1=0\Leftrightarrow25\left(x+1\right)^4-25\left(x+1\right)^2-\left(\left(x+1\right)^2-1\right)=0\)
\(\Leftrightarrow25\left(x+1\right)^2.\left(\left(x+1\right)^2-1\right)-\left(\left(x+1\right)^2-1\right)=0\)
\(\Leftrightarrow\left(\left(x+1\right)^2-1\right).\left(25\left(x+1\right)^2-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}\left(x+1\right)^2-1=0\\25\left(x+1\right)^2-1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0,-2\\x=-\frac{4}{5},-\frac{6}{5}\end{cases}}}\)
\(x^2+x-1=0\Leftrightarrow\left(x+\frac{1}{2}\right)^2-\frac{5}{4}=0\Leftrightarrow\orbr{\begin{cases}x+\frac{1}{2}=\frac{\sqrt{5}}{2}\\x+\frac{1}{2}=\frac{-\sqrt{5}}{2}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{\sqrt{5}-1}{2}\\x=\frac{-\sqrt{5}-1}{2}\end{cases}}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^2-4x-4=25\)
\(\Leftrightarrow x^2-4x+4=33\)
\(\Leftrightarrow\left(x-2\right)^2=33\)
\(\Leftrightarrow\orbr{\begin{cases}x-2=\sqrt{33}\\x-2=-\sqrt{33}\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\sqrt{33}+2\\x=2-\sqrt{33}\end{cases}}\)
\(x^2-4x-4=25\)
\(\Rightarrow x^2-4x-4-25=0\)
\(\Rightarrow x^2-4x-29=0\)
\(\Rightarrow x^2-4x+4-33=0\)
\(\Rightarrow\left(x^2-4x+4\right)-33=0\)
\(\Rightarrow\left(x-2\right)^2=33\)
\(\Rightarrow\left(x-2\right)^2=\left(\sqrt{33}\right)^2=\left(-\sqrt{33}\right)^2\)
\(\Rightarrow\orbr{\begin{cases}x-2=\sqrt{33}\\x-2=-\sqrt{33}\end{cases}\Rightarrow\orbr{\begin{cases}x=2+\sqrt{33}\\x=2-\sqrt{33}\end{cases}}}\)
Vậy \(x\in\left\{2+\sqrt{33};2-\sqrt{33}\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x3 + 3x2 + 3x + 1 = 64
=> (x + 1)3 = 64
=> (x + 1)3 = 43
=> x + 1 = 4 => x = 3
b) x3 + 6x2 + 9x = 4x
=> x3 + 6x2 + 9x - 4x = 0
=> x3 + 6x2 + 5x = 0
=> x3 + 5x2 + x2 + 5x = 0
=> x2(x + 5) + x(x + 5) = 0
=> (x + 5)(x2 + x) = 0
=> (x + 5)x(x + 1) = 0
=> \(\hept{\begin{cases}x=-5\\x=0\\x=-1\end{cases}}\)
c) 4(x - 2)2 = (x + 2)2
=> 4(x2 - 4x + 4) = x2 + 4x + 4
=> 4x2 - 16x + 16 = x2 + 4x + 4
=> 4x2 - 16x + 16 - x2 - 4x - 4 = 0
=> 3x2 - 20x + 12 = 0
=> 3x2 - 18x - 2x + 12 = 0
=> 3x(x - 6) - 2(x - 6) = 0
=> (x - 6)(3x - 2) = 0
=> \(\orbr{\begin{cases}x=6\\x=\frac{2}{3}\end{cases}}\)
d) x4 - 16x2 = 0
=> x2(x2 - 16) = 0
=> \(\orbr{\begin{cases}x^2=0\\x^2=16\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\x=\pm4\end{cases}}\)
e) x4 - 4x3 + x2 - 4x = 0
=> x4 + x2 - 4x3 - 4x = 0
=> x2(x2 + 1) - 4x(x2 + 1) = 0
=> (x2 - 4x)(x2 + 1) = 0
=> x(x - 4)(x2 + 1) = 0
=> \(\orbr{\begin{cases}x=0\\x=4\end{cases}}\)(vì x2 + 1 \(\ge\)1 > 0 \(\forall\)x)
f) x3 + x = 0 => x(x2 + 1) = 0 => x = 0 (vì x2 + 1 \(\ge1>0\forall\)x)
(x-2)2 = 25 => x- 2 = 5
=> x = 7
\(x^2-4x+4=25\)
\(\Leftrightarrow\left(x-2\right)^2=25\)
\(\Leftrightarrow\orbr{\begin{cases}x-2=5\\x-2=-5\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=7\\x=-3\end{cases}}\)